The Effect of IoT and Library Services on Reading Interest of High School Students - Netti Herawati; Bukman Lian; Muhamad Fahmi (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2026)
This study aims to analyze and determine the effect of the Internet of Things (IoT) and library services on the reading interest of high school students in the Ilir Timur 1 District of Palembang. A quantitative approach was employed with a sample of 92 students selected through probability sampling. Data were collected via questionnaires using a 5-point Likert scale across 90 statement items. Analysis utilized simple and multiple linear regression techniques. The findings revealed three significant effects: (1) IoT independently influences students' reading interest; (2) library services independently influence students' reading interest; and (3) both IoT and library services simultaneously exert a significant influence on the reading interest of high school learners in the district. The research innovatively investigates the synergistic influence of technological infrastructure (IoT) and traditional educational resources (library services) on reading engagement within a localized Indonesian context. Schools and education authorities should strategically invest in both digital connectivity and quality library provisions, recognizing their complementary roles in fostering student reading interest. The study contributes empirical evidence to educational technology discourse, validating that reading motivation in the digital age requires integrated enhancement of both physical learning resources and technological access.